2015
DOI: 10.3109/08820139.2015.1070269
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Profiles Reflecting Macrophage Polarization in Aging and Periodontitis Gingival Tissues

Abstract: SUMMARY Recent evidence has determined a phenotypic and functional heterogeneity for macrophage populations. This plasticity of macrophage function has been related to specific properties of subsets (M1, M2) of these cells in inflammation, adaptive immune responses, and resolution of tissue destructive processes. This investigation hypothesized that targeted alterations in the distribution of macrophage phenotypes in aged individuals, and with periodontitis would be skewed towards M1 inflammatory macrophages i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 66 publications
(76 reference statements)
1
72
0
Order By: Relevance
“…Interestingly, our data suggest that M1 is the major phenotype among infiltrating macrophages in the periodontally diseased gingival tissue of experiment mice and that they suppress bone resorption by inhibiting osteoclastogenesis through their production of IL-12 and IFN-␥. Gonzalez et al showed that mixed populations of M1 and M2 are present in the periodontally diseased gingival tissue of nonhuman primates and also that the proportions of polarized macrophages change with aging (38). It was also found that gene expression patterns for M1 macrophages were significantly elevated in periodontally healthy primates compared to those seen with primates with periodontitis (38).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, our data suggest that M1 is the major phenotype among infiltrating macrophages in the periodontally diseased gingival tissue of experiment mice and that they suppress bone resorption by inhibiting osteoclastogenesis through their production of IL-12 and IFN-␥. Gonzalez et al showed that mixed populations of M1 and M2 are present in the periodontally diseased gingival tissue of nonhuman primates and also that the proportions of polarized macrophages change with aging (38). It was also found that gene expression patterns for M1 macrophages were significantly elevated in periodontally healthy primates compared to those seen with primates with periodontitis (38).…”
Section: Discussionmentioning
confidence: 80%
“…Gonzalez et al showed that mixed populations of M1 and M2 are present in the periodontally diseased gingival tissue of nonhuman primates and also that the proportions of polarized macrophages change with aging (38). It was also found that gene expression patterns for M1 macrophages were significantly elevated in periodontally healthy primates compared to those seen with primates with periodontitis (38). However, at this time, determination of the macrophage phenotype in periodontitis and rheumatoid arthritis in human and mouse model remains elusive.…”
Section: Discussionmentioning
confidence: 98%
“…It is now clear that macrophages of different phenotypes play different roles in the immune response, and temporal imbalance or the predominance of one phenotype may lead to pathological changes, including chronic inflammation and fibrosis (Biswas, Chittezhath, Shalova, & Lim, ). Thus, the proportion of pro‐inflammatory M1‐type macrophages and anti‐inflammatory M2‐type macrophages in gingival tissue presents a critical target for monitoring immune responses in subgingival biofilms as well as disease activity across the involved periodontal tissues (Gonzalez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In periodontal inflammation models, macrophages share properties of both M1 and M2. However, M1 macrophages show a predominance over M2 macrophages, suggesting that M1 macrophages probably represent a subset associated with periodontitis [35][36][37].…”
Section: Innate Immune Response In Periodontal Diseasementioning
confidence: 98%